Espial of Concept Difficulties in the New Africans’ Secondary School Mathematics Curriculum: CTCA Recommended - Olasunkanmi Gbeleyi; Peter Okebukola; Fred Awaah; Adam Umar; Rasheed Sanni; Akanbi Moses; Akeem Adebiyi (International Journal of Education and Humanities, 2023)
The value of teaching-learning the subject mathematics has been one of the foremost challenges and concerns of educators. This study employed a mixed method design aimed at investigating difficult concepts in the new senior secondary mathematics curriculum as perceived by students in Ghana and Nigeria. Guided by two research questions and the sample was 1,252 SS 1-3 students from 34 public and 66 private senior secondary (SS). The students are from both urban (62.9%) and rural (35.1%). The mean age of the students was 15 years, the class streams are science, commercial, and arts classes. The instruments were validated and the reliability was established using Cronbach’s Alpha method, and a reliability index of 0.78 using the test-retest method. The data obtained were analyzed using mean ranking in the IBM-SPSS 23 and Ms. Excel for qualitative analysis into themes and graphical representations. From the data gathered, we found 39 topics that students perceived to be difficult in the new mathematics curriculum. It was recommended amongst others that the CTCA should be used for the teaching-learning of mathematics in African schools based on its effectiveness in STEM related subjects in African and beyond